Petrografia da capa doloítica neoproterozoica do sul do cráton amazônico, região de Mirasol d'Oeste, Mato Grosso - GAIA, Valber do Carmo de Souza (2019)
The cap dolomite of Mirassol d’Oeste Formation is placed in the last cryogenian glaciation context (635 Ma) and represents the base of the Araras Group, occurring in the southern border of the Amazon Craton, district of Mirassol d’Oeste, Mato Grosso. The petrographic characterization provides the identification of three carbonate microfacies: dolomudstone, doloboundstone and dolopackstone/dolomudstone. The dolomudstone microfácies is composed for microcrystalline dolomite often neomorphic, changing the crystal size for microspar and pseudospar dolomite. Occurs vugs and móldica porosity and discreet laminations. The doloboundstone microfácies shows also the microcrystalline dolomite commonly neomorphic grading for microspar and pseudospar dolomite. The fenestral porosity is filled by hidrocabon and dolomite’s crystals showing the fenestral lamination (stromatolitic lamination). Furthermore, there is the vug e móldica porosity. The dolopackstone/dolomudstone microfácies differs from dolomudstone in the fenestral lamination and from the doloboundstone because the fenestral lamination is part of megaripples bedding, interpreted from oscillatory flow regime. Moreover, there is lath-shaped cristals of gypsum pseudomorphs, which composition is silicon-aluminous composition (Si, Al e O). The identified diagenetic processes are: 1) eodiagenetic (calcite, silica and gypsum), mesodiagenetic (dolomite and calcite) and telodiagenetic (Fe-oxide/hydroxide) cementation; 2) neomorphism which begging on late marine diagenesis and goes through the burial diagenesis; 3) formation of secondary porosity through fractures, vugs and molds; 4) migration of hydrocarbon which occurs almost simultaneously the formation of euhedral and saddle dolomite cement; 5) pressure dissolution with formation of stylolites; 6 ) formation of authigenic minerals of pyrite, pyrrhotite(?) and Mn, Fe, Ti – oxides; 7) and finally tardi-burial to uplifting dissolution, forming vugs and móldica porosity and mobilizing the hydrocarbon. The dolomite precipitation is associated with microbial activity and the laminations are the result of microbial mats formation that assimilates microcrystalline dolomite. The cap carbonate deposition was placed on moderately deep waters platform environment, with low energy, saturated in Ca2+, MgSO42- and HCO3-, which by the microbial activity becomes favorable for directing precipitation of micritic dolomite.